Eco-friendly and ultra-sensitive electrochemical sensor for sertraline detection in pharmaceuticals and plasma - El-Bahnasawy, Ramy E.; Batakoushy, Hany A.; Ahmed, Hytham M. (BMC chemistry, 2025)
In this work, methylene blue (MB) is electropolymerized to produce a modified glassy carbon electrode (GCE) that will enhance the electrochemical determination of sertraline (SRT), a selective serotonin reuptake inhibitor. The entire material characterization using Fourier transform infrared spectroscopy (FTIR), energy-dispersive X-ray analysis (EDX), and scanning electron microscopy (SEM) verified that the polymeric film of MB dye had successfully formed on the electrode surface. The modified electrode exhibited enhanced electron transfer kinetics, exhibiting ultra-sensitive SRT detection. According to ICH guidelines, Differential pulse voltammetry (DPV) has been used to estimate the limit of detection (LOD) for SRT, with concentrations ranging from 0.5 µM to 30.0 µM. The LOD value was calculated to be 0.28 µM. Voltammetric methods such as cyclic voltammetry, differential pulse voltammetry and electrochemical impedance spectroscopy were employed to investigate the electrooxidation behavior of SRT at various pH levels and scan rates. The results showed that poly methylene blue (PMB)/GCE exhibits improved electroactive surface area and enhanced charge transfer kinetics compared to bare GCE. High sensitivity, selectivity, and recovery percentage (99.08–101.09%) were demonstrated by the modified sensor (PMB/GCE) in detecting SRT in various matrices, including pharmaceutical samples and spiked plasma. The outstanding eco-friendliness and sustainability of the proposed method were thoroughly demonstrated using multiple assessment tools, including Analytical GREEnness (AGREE), AGREEprep, the Complex MoGAPI, and the newly developed Need, Quality, and Sustainability (NQS) index. In comparison to previously reported methods, the Red-Green-Blue (RGB) 12 algorithm proved to be more cost-effective, environmentally sustainable, analytically robust, and exhibited a higher degree of “whiteness.”